Analisis Gaya Bahasa dalam Puisi “Hatiku Selembar Daun” Karya Sapardi Djoko Damono - Hura, Dernius; Giawa, Prillian Putri Cahyani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research is an analysis of the language style contained in the poem “Hatiku Selembar Daun” by Sapardi Djoko Damono. The purpose of the research is to describe the language style used by the author. Poetry as a type of literary work is formed due to the presence of building blocks, one of which is language style (majas). This research uses qualitative research methods. The research source is primary data with literature study data collection techniques. The results of the study show that the majas that the author tends to use in his poem entitled “My Heart is a Piece of Leaf” are comparative majas including personification, hyperbole, and metaphor with the results in the first stanza using the personification language style, the second stanza the hyperbole language style, and the third stanza the metaphor language style